Muslim eschatology in the Book of the Holy Grail - Pereira Mendes, Fernanda (Revista de Filología Románica, 2025)
In this article, we demonstrate the intertextual relationships between the Book of the Holy Grail and one of the main Muslim eschatological narratives, known in medieval Europe as Muhammad’s Ladder. For the comparative analysis, we used the version of the Book of Muhammad’s Ladder commissioned by Alphonse X to the translators of Toledo, in the 13th century, recently translated into Portuguese; and the sixteenth century translation of the Book of the Holy Grail into Portuguese. Whenever appropriate, we resort to the original French text of this work, as well as other versions of the Islamic narrative.